A new Newton’s method with diagonal Jacobian approximation for solving systems of nonlinear equations - Mohammed Waziri, Yusuf; Leong, Wah June; Malik, Abu Hassan; Mansor, Monsi (Universiti Malaysia Perlis (UniMAP), 2010)
1st Regional Conference on Applied and Engineering Mathematics (RCAEM-I) 2010 organized by Universiti Malaysia Perlis (UniMAP) and co-organized by Universiti Sains Malaysia (USM) & Universiti Kebangsaan Malaysia (UKM), 2nd - 3rd June 2010 at Eastern & Oriental Hotel, Penang.